PENENTUAN STATUS KORBAN PEMERKOSAAN GUNA MELAKUKAN ABORSI PASCA PENGESAHAN UNDANG-UNDANG NOMOR 1 TAHUN 2023 - Tsabitha Afnan Putri Wahyudhi (Jurnal Mercatoria, 2023)
This article or writing aims to find a determination when someone can be said to be a victim of sexual violence that causes pregnancy in the context of the victim wanting an abortion procedure according to the provisions of Article 463 Paragraph (2) of Law Number 1 of 2023. This determination is determined so that the fetus does not exceed the age limit of 14 weeks. The problem is focused on determining when someone can be said to be a victim of sexual violence that causes pregnancy in the context of the victim wanting an abortion procedure according to the provisions of Article 463 Paragraph (2) of Law Number 1 of 2023 in the future. In order to approach this problem, the legal justice theory of John Rawles and Aristotle is used as a reference. The data were collected through literature and analyzed qualitatively. This study concludes that the party authorized to determine when a person can have a legal abortion is the investigator and determining the status of a rape victim is during the investigation. This was concluded based on Statute no. 12 of 2022 concerning Criminal Acts of Sexual Violence and Regulation of the Chief of Police (Perkap) No. 6 of 2019 contains the Investigation of Criminal Acts.